ANALISIS CRITICAL STATE LINE DAN INSTABILITY LINE PADA PASIR PETOBO DENGAN KANDUNGAN LANAU 10% BERDASARKAN PENGUJIAN TRIAXIAL CONSOLIDATED UNDRAINED - Latifah Arub Ambarwati; Togani Cahyadi Upomo; Muhammad Ilham Subiantara; Elisa Yuliana; Nila Puspitasari; Adita Narotama; Rizki Heryanto; Lintang Namira Salsabila Andini; Fabian Neopasha Ferdinand Putra (CRANE: Civil Engineering Research Journal, 2026)
This study investigates the mechanical behaviour and instability characteristics of Petobo sand containing 10% silt within the framework of Critical State Soil Mechanics (CSSM). Laboratory testing was conducted employing consolidated undrained (CU) triaxial tests on remolded specimens with varying relative densities after consolidation (Dr,c = 22.65–50.39%) and effective confining pressures (σ′₃ = 100–400 kPa). The analysis focused on stress–strain response, excess pore water pressure generation, and effective stress path evolution to identify the positions of the Critical State Line (CSL) and Instability Line (IL). The results show that all specimens exhibit contractive behaviour accompanied by strain softening after peak strength. The peak deviator stress increased from 18.57 kPa under very loose conditions to 103.48 kPa at higher relative density and confining pressure, indicating a significant influence of density state and effective stress level on shear resistance. Effective stress path analysis reveals that instability occurs prior to reaching the CSL, as indicated by a sharp reduction in deviator stress after the stress path crosses the Instability Line. The obtained IL slope is consistently lower than the CSL slope, with its position influenced by relative density conditions. Furthermore, increasing relative density not only enhances shear strength but also reduces the extent of the potential instability zone in the p′–q stress space. These findings provide new experimental insight into the instability behaviour of Petobo silty sand and contribute to a better mechanistic interpretation of flowslide phenomena in the field.